2014
DOI: 10.1186/1880-5981-66-84
|View full text |Cite
|
Sign up to set email alerts
|

Subgrain boundary analyses in deformed orthopyroxene by TEM/STEM with EBSD-FIB sample preparation technique

Abstract: High-resolution structure analyses using electron beam techniques have been performed for the investigation of subgrain boundaries (SGBs) in deformed orthopyroxene (Opx) in mylonite from Hidaka Metamorphic Belt, Hokkaido, Japan, to understand ductile deformation mechanism of silicate minerals in shear zones. Scanning electron microscopy (SEM) and electron backscatter diffraction (EBSD) analysis of Opx porphyroclasts in the mylonitic rock indicated that the crystal orientation inside the Opx crystals gradually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Similar microstructures have been observed previously both in experimentally deformed aggregates [e.g., Coe , ; Raleigh et al , ; Coe and Muller , ; Coe and Kirby , ] and in natural samples [ Etheridge , ; van Duysen et al , ; Nazé , ; Nazé et al , ; Raimbourg et al , ; Kogure et al , ]. Dissociation of [001] edge dislocations in the (100) plane, according to the reaction c → 1/6 c + 5/6 c , is reported in association with the orthoenstatite‐clinoenstatite transformation; glide of the strong 5/6 [001] partial dislocation then generates the untwinning of one orthorhombic unit cell into two monoclinic unit cells [ Nazé et al , ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar microstructures have been observed previously both in experimentally deformed aggregates [e.g., Coe , ; Raleigh et al , ; Coe and Muller , ; Coe and Kirby , ] and in natural samples [ Etheridge , ; van Duysen et al , ; Nazé , ; Nazé et al , ; Raimbourg et al , ; Kogure et al , ]. Dissociation of [001] edge dislocations in the (100) plane, according to the reaction c → 1/6 c + 5/6 c , is reported in association with the orthoenstatite‐clinoenstatite transformation; glide of the strong 5/6 [001] partial dislocation then generates the untwinning of one orthorhombic unit cell into two monoclinic unit cells [ Nazé et al , ].…”
Section: Discussionsupporting
confidence: 78%
“…Dissociation of [001] edge dislocations in the (100) plane, according to the reaction c → 1/6 c + 5/6 c , is reported in association with the orthoenstatite‐clinoenstatite transformation; glide of the strong 5/6 [001] partial dislocation then generates the untwinning of one orthorhombic unit cell into two monoclinic unit cells [ Nazé et al , ]. Raimbourg et al [] and Kogure et al [] identified the formation of clinoenstatite lamellae between dissociated [001] partials in orthoenstatite, leading to the development of subgrain boundaries in naturally deformed crystals. It is likely that our observations are largely due to this very mechanism, with extensive partial dislocation gliding in the (100) planes during deformation, resulting in some orthoenstatite to clinoenstatite transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Dissociation of [001] edge dislocations in (100) plane, according to the reaction [001] → 1/6[001] + 5/6[001], is also reported in association with the ortho-clinoenstatite transformation at moderate to low temperature; glide of the strong 5/6[001] partial dislocation generates then the "untwinning" of one orthorhombic unit cell into two monoclinic unit cells. Dissociation of [001] dislocation has also been recently observed in naturally deformed crystals, in association with subgrain boundary formation (Kogure et al, 2014). Bruijin and Skemer (2014) estimated recently that, in the upper mantle, orthopyroxenes with grain size larger than ~150-500 µm deform in the dislocation creep regime.…”
Section: Introductionmentioning
confidence: 93%
“…(1)The Nankai trough (14 papers; Sugihara et al 2014, Tsuji et al 2014, Idehara et al 2014, Akuhara and Mochizuki 2014, Hyodo et al 2014, Takahashi et al 2014, Yamada and Shibanuma 2015, Takeshita et al 2014, Hino et al 2015, and Toki et al 2014) (2)The Japan trench (6 papers; Aochi and Ide 2014, Koge et al 2014, Sawai et al 2014, and Boston et al 2014) (3)Other trenches and fault zones (4 papers; Maekawa et al 2014, Namiki et al 2014) and ancient accretionary complexes and faults on land (7 papers; Schumann et al 2014, Hamahashi et al 2015, Kogure et al 2014, and Hashimoto and Yamano 2014) (4)Theoretical treatments of fracture and earthquake (2 papers; Kame et al 2014 andNishiyama et al 2014) The papers are also categorized into three scientific issues, focusing on different regions within each topic:…”
mentioning
confidence: 99%
“…(1)Framework and setting of the seismogenic zone from the view point of seismicity in the Nankai trough (Idehara et al 2014, Akuhara andMochizuki 2014), Japan Trench (Aochi and Ide 2014), Hikurangi margin , or from the geological and geophysical points of view for the Nankai Trough (Tsuji et al 2014, Sugihara et al 2014) and Japan Trench (Boston et al 2014, Koge et al 2014) (2)Material and physical properties or conditions of the fault for the Nankai Trough (Takahashi et al 2014, the Japan Trench (Sawai et al 2014), and the Costa Rica margin (Namiki et al 2014) (3)Analysis of water-rock interaction with faulting in an ancient accretion complex and fault in the Shimanto Belt, Japan (Schumann et al 2014, Hamahashi et al 2015, Chelunpu Fault, Taiwan , Alaska , Median Tectonic Line, Japan , crustal rocks on land (Kogure et al 2014), and theoretical treatment of fracturing, friction, and earthquakes (Nishiyama et al 2014, Kame et al 2014 Traditional research on earthquakes is physics-based, but physico-chemical processes and their geological record in fault rocks, both in active and inactive fossilized rocks, are of recent concern. Many studies of natural records of seismic faulting have been conducted in terms of their physico-chemical processes.…”
mentioning
confidence: 99%